Unveiling Players’ Perceptions of Mother- and Father-Initiated Motivational Climates and Fear of Failure in Youth Male Team Sports - Patrícia Coutinho; Cristiana Bessa; Cláudia Dias; Isabel Mesquita; António M. Fonseca (Sports, 2024)
The aim of this study was to examine the relationship between perceived mother- and father-initiated motivational climates and players’ fear of failure in youth male team sports. A sample of 336 youth male players from five team sports (basketball, football, handball, volleyball, and water polo) completed the Parent-Initiated Motivational Climate Questionnaire-2 and the Performance Failure Appraisal Inventory. The results showed that perceived mother- and father-initiated motivational climates were related to fear of failure predispositions. While a mastery orientation (perceived learning-enjoyment climate) had a low association with fear of failure, an ego orientation (perceived worry-conducive and success-without-effort climates) was highly related to fear of failure. Father-initiated climates had stronger associations with fear of failure than mother-initiated ones, revealing that mothers and fathers may have different influences when considering the developmental origins of fear of failure. The relationships between mother- and father-initiated motivational climates and fear of failure varied according to the type of sport, with basketball, football, and volleyball presenting stronger associations. The dimensions “Fear of important others losing interest” and “Fear of upsetting important others” presented the highest explained variance in all sports when predicted by the father-initiated motivational climate. The findings can inform important evidence-based guidelines and recommendations for parents, coaches, and organizations, enabling them to create supportive environments that aid athletes in developing the necessary psychological skills for long-term success and well-being.